Traditional Chinese Medicine Constitution (TCMC)'s validity and reliability in the Indonesian language - Intansari Nurjannah; Willie Japaries; Tjhia Khie Khiong (Universitas Gadjah Mada, 2021)
Purpose: Traditional Chinese Medicine Constitution (TCMC) is an instrument to measure health condition levels. This study aimed to measure the construct validity and reliability of the TCMC in Indonesia. Methods: Indonesian experts of TCMC checked the TCMC Indonesian translation, then tested it on 50 people to determine whether the items were understood or not. Next, TCMC was used to collect data in community service activities. 391 TCMC data were collected, and after checking data's completeness, there were 377 data for analysis. This study used Pearson correlation for measuring construct validity and Cronbach's alpha for reliability analysis. Results: All items from TCMC were valid with Sig value. (2-tailed) < 0.05. For reliability, the value of Cronbach Alpha on Qi-Deficiency was 0.608 (moderate); Yang-deficiency was 0.728 (high); Yin-deficiency was 0.769 (high); Phlegm-dampness was 0.672 (moderate); Damp-heat was 0,501 (moderate); Blood Stasis was 0.531 (moderate); Qi-stagnation was 0.777 (high); Inherited special was 0.719 (high) and Balanced was 0.727 (high). Conclusions: TCMC in Indonesian is valid and reliable and can be used to measure human health conditions from the perspectives of Traditional Chinese Medicine.